Transcultural adaptation of the REMICOM Test for the assessment of children’s text comprehension monitoring - Formoso, Jesica (2024)
Comprehensive reading is the ability to decode a text, construct its global meaning, and generate a mental representation of it. It is a complex cognitive skill that requires integrating numerous skills and knowledge, including monitoring comprehension during the reading process. This refers to an individual’s ability to regulate their understanding as they read. This study aims to analyze the psychometric properties of a locally adapted version of the REMICOM test, originally designed in Argentina, to assess reading comprehension monitoring in 8- to 10-year-old children. For this purpose, we conducted a pilot study with a sample of 45 third-grade Spanish children from a public school in the city of Granada. We administered a version of the test that included 40 passages, where children were required to identify any problems or contradictory information in them. Out of those statements, 10 were correct, and 30 contained a non-word, an internal inconsistency, or a violation of prior knowledge. We identified the items with the best discrimination capacity to create a final version with 20 items. We obtained measures for validity and reliability. Subsequently, the results were compared with a sample of Argentinean children of the same age. Our findings suggest that the local version of the REMICOM test is a valid and reliable instrument to assess reading comprehension. Additionally, this study contributes to understanding cultural variations in the assessment of reading comprehension monitoring and emphasizes the importance of considering local adaptations in assessment instruments